PENGEMBANGAN MEDIA MAGIC BOX DALAM PEMBELAJARAN MATEMATIKA PADA SISWA KELAS III SDN 13 LUBUKLINGGAU - Indah Meilanda; Satinem Satinem; Elya Rosalina (LP4MK STKIP PGRI Lubuklinggau, 2022)
AbstractThis study aims to be able to develop Magic Box media in learning Mathematics for third grade students of SDN.13 Lubuklinggau and to produce valid and practical media. This type of research is Research and Development using a 4D development model. The subjects in this study were students of class III SDN. 13 Lubuklinggau, totaling 11 students. Data collection techniques used in the form of interviews and questionnaires. Based on the results of the validity test of the three validators, namely linguists, material experts and media experts, the overall average score was 4.27 with a very valid category. While the results obtained from the practicality test of educators and students with an overall average score of 95.31% with a very practical category, so it can be concluded that the Magic Box media has met the valid and practical category and can be used in the mathematics learning process for students. grade III Elementary School.